Lack of cytosolic glutamine synthetase1;2 in vascular tissues of axillary buds causes severe reduction in their outgrowth and disorder of metabolic balance in rice seedlings. (20th December 2014) - Ohashi, Miwa; Ishiyama, Keiki; Kusano, Miyako; Fukushima, Atsushi; Kojima, Soichi; Hanada, Atsushi; Kanno, Keiichi; Hayakawa, Toshihiko; Seto, Yoshiya; Kyozuka, Junko; Yamaguchi, Shinjiro; Yamaya, Tomoyuki
Summary The development and elongation of active tillers in rice was severely reduced by a lack of cytosolic glutamine synthetase1;2 (GS1;2), and, to a lesser extent, lack of NADH‐glutamate synthase1 in knockout mutants. In situ hybridization using the basal part of wild‐type seedlings clearly showed that expression of OsGS1;2 was detected in the phloem companion cells of the nodal vascular anastomoses and large vascular bundles of axillary buds. Accumulation of lignin, visualized using phloroglucin HCl, was also observed in these tissues. The lack of GS1;2 resulted in reduced accumulation of lignin. Re‐introduction into the mutants of OsGS1;2 cDNA under the control of its own promoter successfully restored the outgrowth of tillers and lignin deposition to wild‐type levels. Transcriptomic analysis using a 5 mm basal region of rice shoots showed that the GS1;2 mutants accumulated reduced amounts of mRNAs for carbon and nitrogen metabolism, including C1 unit transfer in lignin synthesis. Although a high content of strigolactone in rice roots is known to reduce active tiller number, the reduction of outgrowth of axillary buds observed in the GS1;2 mutants was independent of the level of strigolactone. Thus metabolic disorder caused by the lack of GS1;2 resulted in a severe reduction in the outgrowth of axillary buds and lignin deposition.